Community Engagement: An Integral Component of a Multifaceted Conservation Approach for the Transboundary Western Pacific Leatherback - Pakiding, Fitryanti; Zohar, Kartika; Allo, Alberto Y. T.; Keroman, Sinus; Lontoh, Deasy; Dutton, Peter H.; Tiwari, Manjula (Frontiers in Marine Science, 2020)
Bycatch in fisheries is one of the greatest threats to marine megafauna such as sea turtles, and the Biodiversity Impact Mitigation Hierarchy (BIMH) has been proposed as an improved and holistic approach for integrating fisheries management with sea turtle conservation. The first three BIMH steps – avoid, minimize, and remediate – take place at sea where fishing activity is taking place. However, these at-sea measures are costly and difficult to effectively implement across the vast range of a highly migratory species. As such, some level of mortality continues, even when the first three steps of the BIMH are implemented as extensively as possible. These remaining negative impacts need to be addressed by compensatory conservation actions elsewhere, e.g., at sea turtle nesting beaches. As a case study, we use the critically endangered leatherback sea turtle nesting population in Papua Barat, Indonesia, to illustrate the opportunity for conservatory offsets to fisheries bycatch across the Pacific. We describe the community empowerment and nest protection programs that have been enhanced by the voluntary offsets from the tuna industry. While improved nest protection measures have helped optimize hatchling production, the engagement of the local communities, through activities that empower and enhance quality of life, has been a critical component to the successful increase in hatchlings. This momentum needs to be sustained and scaled-up to protect the majority of threatened nests over a consistent number of years to successfully provide the recruitment boost needed at the population level. These compensatory off-site conservation measures are also the most cost-effective means of achieving increases in leatherback populations, and perhaps one of the most critical components of the recovery strategy for Pacific leatherbacks.